Partnerships, Action, and Collaboration, Together (PACT): A Community-Based Partnership Where Innovation, Collaboration, and Impact Reshape Stakeholders' Vision - Mary D. Burbank; Melissa M. Goldsmith; Koeun Park Eldredge; Jennifer Spikner (The University of Alabama, 2022)
Project PACT (Partnerships, Action, & Collaboration, Together) (a pseudonym) is a multi-stakeholder partnership that reflects multiple goals, commitments, and priorities for early childhood education. PACT was informed by the literature on community-based research (CBR) and a commitment by partners to strengthen P-3 education where stakeholder assets contributed to reciprocal learning experiences in early childhood education. PACT stakeholders transformed two early childhood education classrooms into Montessori classrooms within a district public school. As one in a series of investigations, this research specifically examined partner commitments to a unique collaboration, the emergence of roles and responsibilities over time, and manifestations of innovation within a traditional public school setting. Data illustrate how stakeholders established a collaboration that allowed for flexibility, perspective-taking, and the opportunity to work together to reconsider and strengthen P-3 education through a model typically reserved for children of affluence. Beyond the operational demands of a startup initiative, findings also reflect the power of a collective through flexibility and a stance that values the assets of a community. The impact of this work demonstrates the potential to successfully impact quality education in early childhood settings through equity and opportunity.